Large-scale association analysis provides insights into the genetic architecture and pathophysiology of type 2 diabetes. - Morris, A; Voight, B; Teslovich, T; Ferreira, T; Segrè, A; Steinthorsdottir, V; Strawbridge, R; Khan, H; Grallert, H; Mahajan, A; Prokopenko, I; Kang, H; et al. (2012)
To extend understanding of the genetic architecture and molecular basis of type 2 diabetes (T2D), we conducted a meta-analysis of genetic variants on the Metabochip, including 34,840 cases and 114,981 controls, overwhelmingly of European descent. We identified ten previously unreported T2D susceptibility loci, including two showing sex-differentiated association. Genome-wide analyses of these data are consistent with a long tail of additional common variant loci explaining much of the variation in susceptibility to T2D. Exploration of the enlarged set of susceptibility loci implicates several processes, including CREBBP-related transcription, adipocytokine signaling and cell cycle regulation, in diabetes pathogenesis.